Herpes simplex virus-2-associated esophagitis in immunocompetent host - Haider A. Naqvi; Sumanthkumar Bandaru; Adrien L. Janvier; Muhammad Nadeem Yousaf (Gastroenterology Review)
Herpes esophagitis (HE) is typically caused by herpes simplex virus type 1 (HSV-1), although less frequently, it is caused by HSV type 2 (HSV-2). Most cases of HE occur in immunocompromised hosts, but occasionally immunocompetent patients develop this condition. Thus, HSV-2 esophageal infection in immunocompetent individuals is comparatively rare [1]. Canalejo Castrillero et al. performed a review of published HE cases (English and Spanish language) in immunocompetent patients from 1950 to 2009. The HSV type was identified in only 27 out 56 cases. However, among the identified cases, 96% (26) were due to HSV-1 and only 4% (1) was due to HSV-2 [1]. The overall reported incidence of HE is 1.8% [2]. Common risk factors for HE include a history of HIV, AIDS, malignancy, solid organs transplant, use of steroids, immunosuppressant medications, chemotherapy, and radiation therapy [1, 3–7]. An estimated 10–15% of bone marrow transplant patients and up to 20% of AIDS patients may develop HE [8]. The mode of esophageal infection in immunocompromised individuals is either viral reactivation or new infection, whereas in immunocompetent individuals, new infection is the primary mode [1].